مسؤولية المتدخل الإقتصادي عن الإخلال بضمان سلامة المستهلك - خمقاني, كريمة (جامعة الوادي University of Eloued, 2017)
أقر المشرع الجزائري بموجب المادة 140 مكرر من القانون المدني، مسؤولية موضوعية أساسها العيب وليس الخطأ، تقوم فيها مسؤولية المتدخل الإقتصادي عند إخلاله بضمان سلامة المستهلك. يستلزم لقيام هذه المسؤولية الموضوعية توافر جملة من الأركان المنصوص عليها في المادة 140 مكرر من القانون المدني المتمثلة في العيب والضرر والعلاقة السببية بينهما. ينتج عن قيام مسؤولية المتدخل الاقتصادي عن إخلاله بضمان سلامة المستهلك التعويض باعتباره أثراً مباشراً، ولم يأخذ المشرع الجزائري بمبدأ تسقيف التعويض باعتباره إجراء في صالح منظومة حماية المستهلك، إذ سيسمح للقاضي إقرار أي تعويض يناسب حجم الضرر الذي أصاب المستهلك عند اقتنائه للمنتوج المعيب. إن عجز نظام المسؤولية المدنية عن تعويض المستهلكين المضرورين أدى إلى الإتجاه نحو إشتراكية وسائل التعويض والتي من بينها التأمين الذي يعد بمثابة ضمان، فأصبح المتدخل يلجأ إلى توزيع عبء التعويض بتقسيم الأقساط بينه وبين المستهلكين من خلال إدماج بعض تبعات هذا القسط في ثمن المنتوجات
Economic Intermediary, Consumer, Compensation, Guarantee.
Keywords: المتدخل الإقتصادي ، المستهلك، التعويض، الضمان; In accordance with Article 140 bis of the Civil Code, the Algerian legislature has approved a responsibility centered on the defect and not on the fault, where the relative responsibility of the economic intervener is made on its defective products thus ensuring the Right of consumers victims. In order to prove this relative responsibility, a set of elements must be combined under Article 140 bis of the Civil Code, namely: the defect, the damage suffered and the causal relationship between them. This act results in remuneration, while the Algerian legislator did not put definitive limits on this remuneration, and it is up to the judge alone to evaluate it according to the damages suffered to the victim consumer when using these products defective. However, the inability of civil liability to ensure the remuneration of the victimized consumers has been due to the adaptation of the collective means of remuneration such as the insurance which consists in sharing the premiums between the intervener and the consumer, Integrating into the price of products